Physicochemical characteristics of shea kernels and kinetics of shea butter press extraction (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Morphological study of some non conventional oil seeds are of great interest for the development of some communities. In this investigation, shea kernels from 4 localities in Chad were studied. The sun dried shea kernels from Beinamar locality had the greatest length (28.30 ±3,25 mm), diameter (20.58 ±2.46 mm), weight (5.56 ±1.52 g) and moisture content (3.79 ± 0.14 %), whereas the kernels of Penie village had the least values (24.25 ± 2.54, 19.02 ± 2.34, 4. 0 ± 1.01 and 3.54 ± 0.33 respectively) of the mentioned characteristics. On the other hand, the total lipid content of Penie’s shea kernels was the highest (58.5%) whereas that of Bolo village was the lowest one (53.53 ± 0.40 %). The acid value of the 4 samples was extremely high (25.31 ± 0.71- 38.30 ± 0.76 mg KOH/g oil), whereas the acid value of the oven dried shea kernels produced using boiling method was low (1.2 - 2.1). The kinetics of press extraction of shea butter suggested that the extraction time is 12 min.